Mediating Effect of Strategic Supply Chain Management on Social and Environmental Sustainability: Evidence from SMEs of Canada, Iran, and Turkey - Adnan ul Haque; Sebastian Kot; Eugene Kozlovski (International Journal of Supply Chain Management, 2019)
Purpose - The cross-sectional comparative study investigates the mediating effect of strategic supply chain management in the SMEs operating in distinctive economies of Canada, Iran and Turkey on the social and environmental sustainability. Methodology - The survey questionnaire is circulated through networking, connections, referral and purposive sampling. The data is collected from 613 SMEs (over 200 in all three countries). Smart partial least square structural equation modeling (SmartPLS-SEM) is employed for the quantitative data analysis. Findings - Results confirmed that irrespective of the type of economies, strategic supply chain management has a statistically significant positive mediating role in improving the social and environmentally sustainable performances. Interestingly, the findings showed that factors of strategic supply chain management have higher positive impact in Canada than Iran and Turkey. Original value - The study offers a practical contribution by offering the managerial implications to improve SMEs performances as well as facilitate the different industries to adopt the research framework to further explore the role of strategic SCM in social and environmental sustainability. Keywords: Strategic supply chain management, social sustainability, environmental sustainability. SMEs, Contrasting Economies